Optimizing Digital Marketing through NIB, Google Maps, and Canva for MSMEs in Gedangan Sidayu Village, Gresik - Dila Komalasari; Niken Hafshah Aabidah; Krisogonus Rexni; Salsabila RK Syaharani (Konsienti : Community Services Journal, 2026)
The development of digital technology encourages micro, small, and medium enterprises (MSMEs) to utilize various digital platforms to develop their businesses. However, some businesses still lack a Business Identification Number (NIP) as their legal business identity, have not utilized Google Maps to increase their business visibility, and have not used Canva as a digital promotional medium. This community service activity aims to optimize digital marketing through outreach and assistance in creating a Business Identification Number (NIP), registering business locations on Google Maps, and training in using Canva. The methods used included outreach, demonstrations, practice, and direct assistance to business owners. The results of the activity showed that participants understood the importance of a Business Identification Number (NIP) as a legal business identity, were able to register their business locations on Google Maps, and were able to create digital promotional media using Canva. Utilizing these three aspects increases customer trust, expands marketing reach, and strengthens the business image. This activity demonstrates that assistance with business legality and the use of digital platforms increases the readiness of MSMEs to face business competition and supports sustainable business development